Senderización y señalética turística para las cascadas San Gregorio en la Parroquia de San Carlos de las Minas del Cantón Zamora, Provincia de Zamora Chinchipe - Condolo Flores, María Guadalupe (2017)
Since the tourism industry in the rural sector, has achieved a constant dynamism in the economy of rural villages that have some feature attractive for tourists, this requires that these areas should have quality infrastructure and tourist facilities. Under this perspective, the present investigation has as main objective to contribute to the development of tourism in the parish, through the proposal of "Senderizacion and tourist signage for the Waterfalls San Gregorio, in the parish of San Carlos of the mines of the canton Zamora, Zamora Chinchipe province". The idea is to establish the number of visits that can accommodate the path and also provide a system of signals with basic information, to facilitate the travel of tourists. Because thanks to the existence of a good signage people will have a trail where to go to the falls without ruining the flora of the place and take care around the waterfalls while avoiding the creation of a great environmental impact. For the development of the proposal was raised three specific objectives: Perform a diagnostic of the rural parish San Carlos of the Mines, propose the senderizacion and signage for the Waterfalls San Gregorio and develop an Environmental Impact Study for the path Waterfalls San Gregorio. The methodology used in this research to obtain results, it was through a set of methods and techniques that made it possible to carry out the study in an appropriate manner, the methods used is the analytical method, synthetic, inductive and deductive methods, in addition to this the techniques for direct observation, interviews, the SWOT matrix and the Leopold matrix. At the same time; it was necessary to use the theory of authors such as: Carla Ricaurte for the lifting of information of the parish, Miguel Cifuentes to determine the load capacity of the path by ensuring their use in a sustainable manner, to the design of the signage took to the rules laid down by the Ministry of Tourism in the tourist signs. As the results of the research will be able to obtain updated information of the parish regarding services, infrastructure, tourist attractions, social and economic aspects. In the same way, updated the tourism inventory, which identified nine sites of hierarchy I. At the same time, it was determined the load capacity of the path with a number of 219 visits per day, thus avoiding alterations in the environment. With regard to the signage was established ten signs, distributed in four panels, five signs of rapprochement and a pictogram. The material used is wood, the dimensions and characteristics of each sign are subject to the rules set by the MINTUR. For the implementation of the proposal was set at a value of $2,299,50; which will be funded in its entirety by the GAD rural parish of San Carlos of mines. Finally, it identified the environmental impacts generated by the implementation of the senderizacion and tourist signage on the path. What made it possible to establish measures of prevention, correction, mitigation; in order to decrease the level of environmental impact, to maintain the environmental quality and ecological balance. In conclusion, it is determined that the signaling plays a very significant role in the world of tourism because it allows you to facilitate the movement of tourists, it is for this reason that the implementation of the project of senderizacion and tourist signage for the Waterfalls San Gregorio, it will be of utmost importance as it will generate and provide socio-economic valuation of natural resources, cultural and services that has the Parish San Carlos of mines. It is recommended to the authorities of the parish of San Carlos GAD, seek the support of other institutions for the implementation of tourism projects that promote the growth of the tourism activity in the parish and becomes a great tourist potential of the Amazon region.